Pengembangan Lembar Kerja Peserta Didik untuk Meningkatkan Keterampilan Berpikir Kritis Siswa pada Materi Aves - Rizi Fadli; Epa Paujiah; Tri Wahyu Agustina (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aimed to design a Student Worksheet (LKPD) to improve students' critical thinking skills on the topic of Aves. The method used was Research and Development (R&D) with the 3D model, consisting of the define, design, and develop stages. The research subjects were students of Class X4 at a school in Bandung Regency, West Java. Data were obtained through validation sheets from a subject-matter expert, a pedagogical expert, and a biology teacher, as well as pretest-posttest questions based on critical thinking indicators. Data were analyzed using the Likert-scale feasibility percentage and the N-Gain test. The results showed that the developed LKPD was categorized as feasible to highly feasible according to the three validators, and was shown to improve students' critical thinking skills at a moderate level. Therefore, the developed LKPD is suitable for use in instruction and effective in improving students' critical thinking skills on the topic of Aves. Keywords: Aves, Biology Education, Critical Thinking Skills, LKPD, Research and Development